Need assessment of the development the retired training model in pencak silat - Dewi Nurhidayah; Siswantoyo Siswantoyo; Ela Yuliana; Dinan Mitsalina; Dwi Astuti (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2024)
The retired training model is a training model specifically designed for former athletes. This is done to maintain the fitness and health of athletes when they enter retirement. Because in retirement, former athletes are no longer under the coach's control. This study aims to determine the need assessment for developing the Retired training model in the sport of pencak silat. This research is a survey research. There were 145 subjects involved in this study consisting of 58 former pencak silat athletes, 45 active fighters and 42 trainers. The instrument used in this study used a questionnaire distributed via the google form. The data analysis technique used in this study is descriptive statistics using a percentage formula. The results showed that 98% of retired athletes stated the need to develop training models for the retired period. Athletes and coaches 100% stated the need for a training model for the retired period. In this way, it can be concluded that the development of training models to maintain health in retirement in the pencak silat sport is very much needed. The findings in this research can be a basis for the initial product development stages in developing an exercise model to maintain fitness in retired athletes from the pencak silat sport.